Implementation of STEM Integrated Problem Based Learning Model to Improve Problem Solving Skills and Learning Motivation of Grade X Vocational High School Students on the Material of Substances and Their Changes - Sudirman Nur; Jaslin Ikhsan (Postgraduate, University of Mataram, 2024)
This study aims to analyze significant differences in problem-solving ability and learning motivation simultaneously between experimental class students and control class students; problem-solving ability between experimental class students and control class students; learning motivation between experimental class students and control class students; analyze the effective contribution of learning using PBL-STEM to students' problem-solving ability and learning motivation simultaneously; analyze the effective contribution of learning using PBL-STEM to students' problem-solving ability; analyze the effective contribution of learning using the PBL-STEM model to students' problem-solving motivation. This study uses a quasi-experimental model with a posttest only design. The sample of this study consisted of two classes, namely the experimental class and the control class, by random sampling. The experimental class uses learning with PBL-STEM, while the control class uses learning with a scientific approach. Data collection on problem-solving ability was obtained from descriptive test data and learning motivation data through a questionnaire. The MANOVA test was used to analyze the differences in problem-solving ability and learning motivation of experimental and control class students simultaneously. The between subject effect test was used to analyze the differences in each dependent variable in the experimental class and the control class. The partial eta square test was used to analyze the effective contribution of PBL-STEM to the dependent variable. The results showed that there were differences in problem-solving ability and learning motivation simultaneously between students in the experimental group and the control group; there were significant differences in problem-solving ability between students in the experimental group and the control group; there were significant differences in learning motivation between students in the experimental group and the control group; the effective contribution of using PBL-STEM to problem-solving ability and learning motivation simultaneously was 24.6% (high); the effective contribution of using PBL-STEM to problem-solving ability was 19% (high); the effective contribution of using PBL-STEM to learning motivation was 15.7% (high).